Density Fluctuations of Hard-Sphere Fluids in Narrow Confinement - Kim Nygård (Physical Review X, 2016)
Spatial confinement induces microscopic ordering of fluids, which in turn alters many of their dynamic and thermodynamic properties. However, the isothermal compressibility has hitherto been largely overlooked in the literature, despite its obvious connection to the underlying microscopic structure and density fluctuations in confined geometries. Here, we address this issue by probing density profiles and structure factors of hard-sphere fluids in various narrow slits, using x-ray scattering from colloid-filled nanofluidic containers and integral-equation-based statistical mechanics at the level of pair distributions for inhomogeneous fluids. Most importantly, we demonstrate that density fluctuations and isothermal compressibilities in confined fluids can be obtained experimentally from the long-wavelength limit of the structure factor, providing a formally exact and experimentally accessible connection between microscopic structure and macroscopic, thermodynamic properties. Our approach will thus, for example, allow direct experimental verification of theoretically predicted enhanced density fluctuations in liquids near solvophobic interfaces.